25-Hydroxyvitamin D insufficiency is associated with cardiometabolic risk in Korean adolescents: the 2008–2009 Korea National Health and Nutrition Examination Survey (KNHANES). Issue 1 (20th November 2012) - Nam, Ga Eun; Kim, Do Hoon; Cho, Kyung Hwan; Park, Yong Gyu; Han, Kyung Do; Kim, Seon Mee; Lee, Seung Hwan; Ko, Byung Joon; Ji Kim, Min
Abstract: Objective: Vitamin D insufficiency is known to be related to cardiometabolic disorders; however, the associations among serum 25-hydroxyvitamin D (25(OH)D) concentration and metabolic syndrome and cardiometabolic risk factors in children and adolescents have not yet been clearly delineated. For this reason, we investigated the relationship among serum 25(OH)D concentration and metabolic syndrome and cardiometabolic risk factors among Korean adolescents. Design: We performed a cross-sectional analysis and used hierarchical multivariate logistic regression analysis models to adjust for confounding variables. Setting: We used the data gathered during the 2008–2009 Korea National Health and Nutrition Examination Survey (KNHANES). Subjects: Our subjects included 1504 Korean adolescents aged 12–18 years who participated in the KNHANES. Results: Vitamin D insufficiency, defined as 25(OH)D concentration <50 nmol/l, was found in 75·3 % of Korean adolescents and was associated with an increased risk of the prevalence of metabolic syndrome. Waist circumference and BMI were the most closely correlated cardiometabolic components of metabolic syndrome according to serum 25(OH)D status, but no significant relationship was found between serum 25(OH)D concentration and insulin resistance or for the risks for high blood pressure, hyperglycaemia, reduced HDL-cholesterol or hypertriacylglycerolaemia, with or without adjustment for confounding variables. Conclusions: Low serum 25(OH)D concentration appears to be associated with several cardiometabolic risk factors and an increased risk of the prevalence of metabolic syndrome in Korean adolescents.